Social isolation is linked to classical risk factors of Alzheimer's disease-related dementias. - Kimia Shafighi; Sylvia Villeneuve; Pedro Rosa Neto; AmanPreet Badhwar; Judes Poirier; Vaibhav Sharma; Yasser Iturria Medina; Patricia P Silveira; Laurette Dube; David Glahn; Danilo Bzdok (PLoS ONE, 2023)
Alzheimer's disease and related dementias is a major public health burden-compounding over upcoming years due to longevity. Recently, clinical evidence hinted at the experience of social isolation in expediting dementia onset. In 502,506 UK Biobank participants and 30,097 participants from the Canadian Longitudinal Study of Aging, we revisited traditional risk factors for developing dementia in the context of loneliness and lacking social support. Across these measures of subjective and objective social deprivation, we have identified strong links between individuals' social capital and various indicators of Alzheimer's disease and related dementias risk, which replicated across both population cohorts. The quality and quantity of daily social encounters had deep connections with key aetiopathological factors, which represent 1) personal habits and lifestyle factors, 2) physical health, 3) mental health, and 4) societal and external factors. Our population-scale assessment suggest that social lifestyle determinants are linked to most neurodegeneration risk factors, highlighting them as promising targets for preventive clinical action.